2021
DOI: 10.1051/e3sconf/202125807021
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ readiness to use ICT in the conditions of inclusive education

Abstract: This article focuses on the formation of future pre-school teachers’ readiness to use the information and communication technologies (ICT) in the conditions of inclusive education and their training at universities. Authors justify the necessary of formation students’ capability in modern ICT area. In the article, using of the ICT in the conditions of inclusive education for the eldest pre-school children is identified based on the theoretical analysis of scientific literature. The article shows survey results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In this study, EFL teachers concede the learning facilities of educational technologies in enhancing motivation, providing feedback, and updating the traditional teaching approaches. These conclusions support studies by Michaeli, et al (2020) andOralbekova, et al (2021), which indicated that it is significant to develop the psychological readiness of teachers to use ICTs in comprehensive pedagogy and learning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, EFL teachers concede the learning facilities of educational technologies in enhancing motivation, providing feedback, and updating the traditional teaching approaches. These conclusions support studies by Michaeli, et al (2020) andOralbekova, et al (2021), which indicated that it is significant to develop the psychological readiness of teachers to use ICTs in comprehensive pedagogy and learning.…”
Section: Discussionsupporting
confidence: 90%
“…According to Rani (2017), considering the implementation of technology in the teaching/learning process, teachers must develop the knowledge and competencies compulsory to utilize ICT in their classroom instruction. Oralbekova, Begalieva, Ortaeva, Magauova, and Suleimen(2021)indicate that it is significant to develop the readiness and willingness of pre-service teachers to use Information Technologies in comprehensive pedagogy and learning.…”
Section: Towards a Technology Shift: Major Merits And Challengesmentioning
confidence: 99%
“…According to (Park & Son, 2022) considering the implementation of technology in the teaching/learning process, teachers must develop the knowledge and competencies required compulsory to utilize ICT in their classroom instruction. Oralbekova et al (2021) indicate that it is significant to develop the readiness and willingness of pre-service teachers to use Information Technologies in comprehensive pedagogy and learning. Therefore, the hypotheses provided in this research are:…”
Section: Literature Review Psychological Engagementmentioning
confidence: 99%
“…The scientific paper by Oralbekova et al (2021) delves into the crucial aspect of preparing future pre-school teachers for the effective utilization of Information and Communication Technologies (ICT) within the context of inclusive education, particularly during their training at universities. A notable contribution of the article is the introduction of the structural and content model that outlines the framework for cultivating the necessary skills and knowledge in pre-service teachers to effectively integrate ICT in inclusive educational settings.…”
Section: Theoretical Overviewmentioning
confidence: 99%